Children's clothing and funeral attire in the 10th to 12th centuries in Finland - Wright, Krista; Sahramaa, Jenni; Berghe, Ina Vanden (Archaeological Textiles Review, 2023)
Four Late Iron Age (900 to 1200 CE) child burials with textile remains were examined to deepen knowledge about child clothing during the Viking Age and Crusade period in Finland. As child burials are rare, an examination of the textile fragments enriches current understandings of children’s outfits. The textiles are made of wool and have survived attached to copper alloy jewellery and copper alloy spiral wire ornaments. Twills, a tabby, braids, tablet-woven bands, as well as dyes and evidence of furs were recognised. The textiles contained many elements that are known in the adult graves, but the thread counts are higher and the wool type softer, possibly made of lambswool.